A randomized controlled pilot study of VO2 max testing: a potential model for measuring relative in vivo efficacy of different red blood cell products. Issue 3 (23rd November 2016) - Bennett‐Guerrero, Elliott; Lockhart, Evelyn L.; Bandarenko, Nicholas; Campbell, Mary L.; Natoli, Michael J.; Jamnik, Veronika K.; Carter, Timothy R.; Moon, Richard E.
Abstract : BACKGROUND: Randomized trials, for example, RECESS, comparing "young" (median, 7‐day) versus "middle‐aged" (median, 28‐day) red blood cells (RBCs), showed no difference in outcome. These data are important; however, they do not inform us about the safety and effectiveness of the oldest RBCs, which some patients receive. It may not be feasible to conduct a clinical trial randomizing patients to receive the oldest blood. Therefore, we propose strenuous exercise (VO2 max testing) as a model to study the relative efficacy to increase oxygen delivery to tissue of different RBC products, for example, extremes of storage duration. STUDY DESIGN AND METHODS: In this pilot study, eight healthy subjects had 2 units of leukoreduced RBCs collected by apheresis in AS‐3 using standard methods. Subjects were randomized to receive both (2) units of their autologous RBCs at either 7 or 42 days after blood collection. VO2 max testing on a cycle ergometer was performed 2 days before (Monday) and 2 days after (Friday) the transfusion visit (Wednesday). This design avoids confounding effects on intravascular volume from the 2‐unit blood transfusion. The primary outcome was the difference in VO2 max between Friday and Monday (delta VO2 max). RESULTS: VO2 max increased more in the 7‐day RBC arm (8.7 ± 6.9% vs. 1.9 ± 6.5%, p = 0.202 for comparison between arms). Exercise duration (seconds) increased in the 7‐day RBC arm (8.4 ± 1.7%) but actually decreased in the 42‐day arm (−2.6 ± 3.6%, p = 0.002). CONCLUSIONS: This pilot study suggests that VO2 max testing has potential as a rigorous and quantitative in vivo functional assay of RBC function. Our preliminary results suggest that 42‐day RBCs are inferior to 7‐day RBCs at delivering oxygen to tissues.